Physico-chemical characteristics of wastewater from a ball mill facility in small-scale gold mining area of Paracale, Camarines Norte, Philippines - Samaniego, Jessie O.; Tanchuling, Maria Antonia N. (2018)
Small-scale gold miners in Paracale, Camarines Norte use amalgamation process to recover gold from mined ores. In the process, they dispose untreated wastewater to water bodies. In this study, wastewater from an active SSGM ball mill facility in the area was analyzed for physico-chemical parameters and heavy metal concentrations. A total of 40 samples were gathered from the ball mill facility while in full operation and were analyzed for heavy metals (As, Ba, Cd, Hg, Pb). Results showed that all metals (except for Ba) exceed the effluent regulatory limits including Hg (0.1768 mg/L) and Pb (9.3821 mg/L), which are 44 and 94 times higher than the limit, respectively. Presence of Hg concentration in the wastewater confirms the miners? illegal use of Hg in amalgamation process. Based on the mercury balance in amalgamation, around 16.8% of total Hg input goes to the sediment and some 0.21% mixed with wastewater and the bulk 82.99% is in the form of amalgam that becomes Hg vapor after burning. Physico-chemical parameters ? temperature, pH, and true color ? are within their respective effluent regulatory limits for Class C waters, while TSS (3,596.9 mg/L) is 36 times higher than the 100 mg/L limit. Other parameters, though not regulated, such as ORP (343.9 mV), turbidity (> 800 NTU), and apparent color (9,880 PCU) were analyzed with high concentrations. From this study, wastewater treatment is recommended before disposing of to the receiving waters to reduce the concentration of heavy metals and TSS. Also, the full and strict implementation of the people?s small-scale mining law must be maintained to protect human health as well as the environment from the adverse effect of the use of Hg in SSGM processes